201k views
3 votes
3y^2-8y+4 factor each polynomial

2 Answers

7 votes

Answer:

(3x - 2)(x - 2)

Explanation:

When factoring this, we know we will get something of the form (ax + b)(cx + d), which expands to ac(x^2) + (ad + bc)x + bd. Because ac = 3, and 3 is prime, a is 3 and c is 1, or vice versa. Knowing this, we have 3d + b = -8 and bd = 4. Guess and check reveals b and d are -2, and the answer is (3x - 2)(x - 2).

User Saqueib
by
5.5k points
5 votes

Answer:

(3y-2) (y-2)

Explanation:

3y^2 -8y+4

We need to factor the polynomial

(3y ) (y )

4 factors into 4*1 and 2*2

We need it to be negative since we have a negative 8

3*-2 -2*1 = -6-2 = -8

-2*-2 = 4

So we have our factors

(3y-2) (y-2)


User Srikan
by
5.5k points